On the new culture of time, child-rearing and acceleration civilisation - Segiet, Katarzyna (Kultura-Społeczeństwo-Edukacja, 2019)
The ‘more, faster, better’ rule accompanies a modern child from the earliest stage of their life. Recently research on child development has become increasingly important and taken on a new dimension. Its significance lies in the capacity to provide important information about core values in child life. It also offers new development opportunities for educational environment for individuals, groups and institutions, working in the field of pedagogy, treating childhood as a common good which needs protection from increasing pressure of time and detrimental effects of acceleration civilisation.